2016
DOI: 10.1163/18759866-08502004
|View full text |Cite
|
Sign up to set email alerts
|

Triadobatrachus massinoti, the earliest known lissamphibian (Vertebrata: Tetrapoda) re-examined by μCT scan, and the evolution of trunk length in batrachians

Abstract: Triadobatrachus massinoti is a batrachian known from a single fossil from the Early Triassic of Madagascar that presents a combination of apomorphic salientian and plesiomorphic batrachian characters. Herein we offer a revised description of the specimen based on X-ray micro-tomography data. We report previously unknown caudal vertebrae, possible mentomeckelians, and hidden parts of other structures. We also confirm the presence of a ventrolateral ledge on the opisthotic, and we rectify some previous interpret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
62
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 56 publications
(103 reference statements)
4
62
0
Order By: Relevance
“…Triadobatrachu s is believed to have inhabited riparian forests or woodlands in or near floodplains, a suitable environment for a walker/hopper (Sigurdsen et al., ; Lires et al., ; Ascarrunz et al., ). Many additional distinct anatomical features involved in the locomotion of modern anurans appear by the Early Jurassic, as found in Prosalirus bitis (Shubin and Jenkins, ).…”
Section: Discussionmentioning
confidence: 99%
“…Triadobatrachu s is believed to have inhabited riparian forests or woodlands in or near floodplains, a suitable environment for a walker/hopper (Sigurdsen et al., ; Lires et al., ; Ascarrunz et al., ). Many additional distinct anatomical features involved in the locomotion of modern anurans appear by the Early Jurassic, as found in Prosalirus bitis (Shubin and Jenkins, ).…”
Section: Discussionmentioning
confidence: 99%
“…Ascarrunz et al . () re‐assessed saltatorial performance of the basalmost and oldest stem‐anuran Triadobatrachus massinoti , from early Triassic. These authors suggested that the trunk of these animals mostly reflects the nonelongated ancestral condition and confirmed previous hypotheses that they were probably not specialized jumpers (Ascarrunz et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Anuran body shape presents specializations associated with jumping performance that are old and phylogenetically conserved, being present in their most basic aspects in fossils from the Jurassic period (Shubin & Jenkins, 1995). Ascarrunz et al (2016) re-assessed saltatorial performance of the basalmost and oldest stem-anuran Triadobatrachus massinoti, from early Triassic. These authors suggested that the trunk of these animals mostly reflects the nonelongated ancestral condition and confirmed previous hypotheses that they were probably not specialized jumpers (Ascarrunz et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite an increase in knowledge on the fossil record of lissamphibians (e.g. Gao & Shubin, 2003;Jenkins, Walsh & Carroll, 2007;Skutschas & Martin, 2011;Ascarrunz et al, 2016), their interrelationship as well as their origin (or origins) from the vast range of early tetrapods remains a matter of debate (Laurin & Reisz, 1997;Meyer & Zardoya, 2003;Schoch & Milner, 2004;Ruta, Coates & Quicke, 2003;Ruta & Coates, 2007;Sigurdsen & Green, 2011;Marjanovi c & Laurin, 2013;Schoch, 2014;Pardo, Small & Huttenlocker, 2017a;Pardo et al, 2017b). Most authors consider lissamphibians as a monophyletic group of extant tetrapods including caecilians (gymnophionans), salamanders (urodeles) and frogs (anurans) that plesiomorphically possess a biphasic life cycle with an aquatic larval stage that metamorphoses into a mainly terrestrial adult stage.…”
Section: Introductionmentioning
confidence: 99%